2010
DOI: 10.1111/j.1600-0609.2009.01378.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response to immunosuppressive therapy with antithymocyte globulin and cyclosporine and prognostic factors for survival in patients with severe aplastic anemia

Abstract: Pre-IST neutrophil counts might predict the response to IST, while absolute ARCs prior to IST and response status after IST could be prognostic factors following IST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
38
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 14 publications
6
38
3
Order By: Relevance
“…For example, in another recent study, higher ANC was also shown to be predictive of response. 30 Baseline ANC was also correlated with response in our study in univariable analysis, but was not seen to be an independent predictor in multivariable analysis once the impact of PNH clone and baseline ARC were taken into account (P=0.64).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…For example, in another recent study, higher ANC was also shown to be predictive of response. 30 Baseline ANC was also correlated with response in our study in univariable analysis, but was not seen to be an independent predictor in multivariable analysis once the impact of PNH clone and baseline ARC were taken into account (P=0.64).…”
Section: Discussionmentioning
confidence: 51%
“…Higher ALC and ARC were previously correlated with a higher survival rate 19 while in another study, only higher ARC was predictive. 30 As with response, distinct prognostic groups could be defined by using a simple scoring system to combine the effects of age and pretreatment ANC and ALC. The survival rate at 5 years for patients with two or fewer poor survival features was 71±9% compared to 16±10% for those with more than two poor survival features (P<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The utility of ARC in predicting IST outcomes has been confirmed in a proportion of reports, but not in others [12,[14][15][16][17]. Higher absolute neutrophil count (ANC) appears to be correlated with a better response rate of IST [15,18]; however, this result was not confirmed in Japanese and German children [12,19,20]. Further, the study of Japanese children demonstrated that lower white blood cell (WBC) count was indicative of a better response to IST rather than higher ANC [12].…”
Section: Pre-treatment Peripheral Blood Countsmentioning
confidence: 99%
“…When the two predictive parameters of ARC and ALC were combined, patients with higher baseline ANC and ARC had a response rate 40 % higher than those with lower baseline ANC and ARC (83 vs 41 %, p < 0.0001). The utility of ARC in predicting IST outcomes has been confirmed in a proportion of reports, but not in others [12,[14][15][16][17]. Higher absolute neutrophil count (ANC) appears to be correlated with a better response rate of IST [15,18]; however, this result was not confirmed in Japanese and German children [12,19,20].…”
Section: Pre-treatment Peripheral Blood Countsmentioning
confidence: 99%
“…[17][18][19] No published series of patients with aplastic anemia has shown that rabbit-ATG is superior to horse-ATG in the context of first-line IST. [16][17][18][19][20][21][22] To date, there have only been a few reports on the efficacy of IST with rabbit-ATG in patients with MDS. 10,23,24 In this study, we compared the outcome of IST using horse-ATG with that of IST using rabbit-ATG in a large series of children with RCC.…”
mentioning
confidence: 99%